Hukum Adat di Aceh: Menakar Eksistensi dan Kedudukannya dalam Sistem Hukum Nasional - Maulana Ira (Lembaga Pengembangan Kinerja Dosen, 2025)
This paper discusses the existence and position of customary law in Aceh, which has long grown and developed within the Acehnese community, as well as its recognition within the national legal system. The 1945 Constitution recognizes the existence of customary law communities and their traditional rights, as stated in Article 18B (2), which indicates the special and unique position of customary law within Indonesia's legal system. In Aceh, the position of customary law is clearly visible, especially since the enactment of Law No. 11 of 2006 on the Governance of Aceh, which further strengthens the position of Acehnese customary law in the national legal system. The recognition of customary law in the Indonesian constitution is expected to have a positive impact on the sustainability of customary law’s existence in Aceh and across Indonesia. Customary law in Aceh, with its various implementations, has become an inseparable part of the country's legal structure and the culture of the Acehnese people. Therefore, it is hoped that the recognition and protection of customary law will continue to evolve, creating a balance between customary legal norms and national law.